Pengenalan Budaya Jepang Melalui Pelatihan Kaligrafi Jepang (Shodou) Pada Mahasiswa Prodi Pariwisata Budaya Dan Keagamaan - Dewi, Ni Putu Sasmika (IAHN Gde Pudja Mataram, 2024)
The application of soft skills and hard skills is crucial in the process of preparing high-quality, resilient, and skilled human resources. One way to enhance the preparation of such human resources is by improving foreign language skills. The Tourism and Religious Culture Study Program is the only program at the Institut Agama Hindu Negeri (IAHN) Gde Pudja Mataram that offers a Japanese language course. Unfortunately, the three-credit hour per meeting course duration is insufficient for learning about Japanese arts, culture, and traditions. Therefore, additional time is needed to study these aspects. The six-day community service activity was conducted to accommodate students' desire to learn more about the Japanese language, particularly kanji characters. By using Japanese calligraphy (shodou) training methods, this training activity was perceived as more interesting and enjoyable. The materials presented in this activity included an introduction to various ways of writing Japanese characters, an introduction to kanji characters and their writing principles, an introduction to Japanese culture and philosophy through shodou training, and practice writing the kanji character tsuyu (露) using shodou techniques. The result of this activity was that students could easily remember the kanji characters they learned because they wrote them repeatedly. Additionally, students were motivated to practice other kanji characters using shodou techniques, as they found that kanji characters written with shodou were more beautiful and appealing than those written in the usual way.